Equilibrium distribution coefficients during osmotic dehydration of apricot - Togrul, Inci Tuerk; Ispir, Ayse (Inst Chemical Engineers, 2008)
The effect of initial osmotic solution concentration (40-70%, w/w), solution temperature (25-45 degrees C), pretreatment before osmotic dehydration (by using chemicals such as K(2)S(2)O(5), Na(2)S(2)O(5), ethyl oleat + K(2)S(2)O(5), ethyl Cleat + Na(2)S(2)O(5) and ethyl Cleat + K(2)CO(3)) and the ratio of the sample to solution (1/4-1/25) on equilibrium distribution coefficients of apricot were investigated during osmotic dehydration. The various osmotic agents such as sucrose, fructose, glucose, maltodextrin and sorbitol were used in osmotic dehydration of apricot. The distribution coefficients of water ranged from 1.893 to 0.822 g g(-1) for various concentrations, 1.302-0.651 g g(-1) for different temperatures, 2.013-0.560 g g(-1) for application of pretreatment and 1.126-0.822g g(-1) for the ratio of the sample to solution, respectively, while the distribution coefficient for solid varied from 1.473 to 0.719 g g(-1) for various concentrations, 0.933-0.719 g g(-1) for various temperatures, 1.427-0.453 g g(-1) for application of pretreatment and 0.916-0.718 g g(-1) for sample to solution ratio, respectively. The distribution coefficient for water decreased with increasing temperature and decreasing sample to solution ratio, and with the increase in syrup concentration it increased or decreased with respect to osmotic agent type. The distribution coefficient for the solid was increased with both an increase in temperature and a decrease in the sample to solution ratio, though it decreases with an increase in syrup concentration. A nonlinear regression of experimental data was carried out to correlate the cumulative relationship between distribution coefficient and syrup concentration. In addition to modeling of the effect of the sample to solution ratio on distribution coefficients of apricots, whole developed models have been tested by using statistical analyses such as chi(2), mean bias error (MBE) and root mean square error (RMSE). (C) 2008 The Institution of Chemical Engineers. Published by Elsevier B.V. All rights reserved.
Keywords: Apricot; Equilibrium distribution coefficient; Osmotic dehydration; Mass transfer